A new multiscale tool for simulating smart-grid energy management based on a systemic approach. (September 2021) - Randriantsoa, Ando Ny Aina; Fakra, Damien Ali Hamada; Ranjaranimaro, Manitra Pierrot; Rachadi, Mohamed Nasroudine Mohamed; Gatina, Jean Claude
Abstract: Electricity needs are growing rapidly in developing countries. Some governments are encouraging the integration of renewable energy into the electrical grid to deal with the environmental issues, depletion issues, and pollution issues from current conventional power generation systems. Therefore, a reliable tool is needed to manage this energy mix. A tool based on two new different strategies is proposed for the management of smart grids. A comparison with the HOMER software was carried out to ensure the reliability of the proposed tool to simulate the management of this energy mix. Furthermore, this tool is capable of simulating the management of energy-mix flows from a building to a country. Users can visualize the simulated environment in a two-dimensional map and graphs of the energy mix management associated with this environment. This approach can serve as a decision-support tool, for instance, in the implementation of a new photovoltaic field or wind turbines. Graphical abstract: Highlights: SMARTEN is a multiscale tool that simulates the management of energy flows in a smart grid. SMARTEN performs simultaneously the simulation of several buildings to an entire country for an hour to an entire year. Reliability tests were carried out by the comparison with the HOMER software. The 2D visualization in SMARTEN allows users to decide on a renewable energy implementation through a time and space view.